Neuropaty Detection In Diabetes Mellitus Patients - Agus Yunianto (Science Midwifery, 2022)
Diabetes mellitus (DM) is a metabolic disease that contains a collection of symptoms that arise in a person caused by an increase in blood glucose levels (hyperglycemia) due to a progressive decrease in insulin secretion, the prevalence of Diabetes Mellitus in the world continues to increase every year. Type 2 diabetes mellitus is a chronic disease that is increasing in the world and is the cause of various organ damage, one of which is diabetic peripheral neuropathy. Early detection of diabetic peripheral neuropathy and identification of risk factors can reduce the morbidity of diabetic peripheral neuropathy. Cases of diabetic neuropathy affect as many as 54% of patients with type 2 diabetes, the prevalence of neuropathy in patients with diabetes mellitus is approximately 30% in hospital patients and 20% in patients in the community. Complications of neuropathy can strike patients with diabetes mellitus at various ages. The longer a patient has diabetes, the risk of developing complications of Diabetes Mellitus will increase. The cause of this is due to degenerative factors, namely a decrease in body functions, especially the ability of pancreatic -cells to produce insulin and other organs of the body that also perform compensatory mechanisms during persistent hyperglycemia. The purpose of this study is to find a simple test that can be used by the public in detecting diabetes mellitus neuropathy, while the data collected by researchers from 2013 to 2018 used 3 databases (Pubmed, ScienceDirect, Google Scholar). So the results of this study explain that the Sudoscan method is a test that does not require special preparation and can be used by untrained people, of course, in detecting neuropathy in diabetes mellitus, while the neuropad method can be carried out by non-professional staff and takes 9 minutes to 13 minutes. minutes and is now easy to use. These methods are very effective, and do not require tools and can be used by the general public, so they can be used to detect neuropathy both in hospitals, health centers and in patients' private places.